2019
DOI: 10.3389/fmicb.2019.02800
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Inhibits Biofilm Formation and the Quorum-Sensing System by Regulating the MsrA Drug Efflux Pump in Staphylococcus saprophyticus

Abstract: Staphylococcus saprophyticus (S. saprophyticus) is one of the main pathogens that cause serious infection due to its acquisition of antibiotic resistance. The efflux pump decreases antibiotic abundance, and biofilm compromises the penetration of antibiotics. It has been reported that baicalin is a potential agent to inhibit efflux pumps, biofilm formation, and quorum-sensing systems. The purpose of this study was to investigate whether baicalin can inhibit S. saprophyticus biofilm formation and the quorum-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…A lot of of approaches have been reported for inhibiting the efflux pump activity including the downregulation of efflux pump genes [42]. Wang et al [43] investigated the MsrA efflux pump inhibitory effect of Baicalin on Staphylococcus saprophyticus . The results showed that Baicalin significantly reduced the efflux of EtBr and downregulated the mRNA transcription level of MsrA gene.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of of approaches have been reported for inhibiting the efflux pump activity including the downregulation of efflux pump genes [42]. Wang et al [43] investigated the MsrA efflux pump inhibitory effect of Baicalin on Staphylococcus saprophyticus . The results showed that Baicalin significantly reduced the efflux of EtBr and downregulated the mRNA transcription level of MsrA gene.…”
Section: Discussionmentioning
confidence: 99%
“…A qRT-PCR was carried out according to the methods previously described [35]. Briefly, ATCC 33591 was cultured in MHB overnight and treated with sub-inhibitory concentrations of BDMC for 4 h. The sample without BDMC was taken as a control.…”
Section: Reverse Transcription and Qrt-pcrmentioning
confidence: 99%
“…On the other hand, PK is known to be a critical enzyme in catalyzing the final step of glycolysis, which involves the transfer of a phosphoryl group from phosphoenolpyruvate to ADP, producing pyruvate and ATP [32]. Recently, it was identified as a "superhub", listed among the top 1% of all interacting proteins in S. aureus and found to be a key regulator of the quorum-sensing system and the biofilm formation process in staphylococci [33][34][35]. Considering these points together with the structural similarity of our compounds (1-3) to previously well-known topoisomerase inhibitors, we selected Staphylococcus DNA gyrase-B and PK as possible molecular targets to mediate the observed antibacterial and antibiofilm activities of the induced phenazine derivatives toward S. aureus.…”
Section: In Vitro Enzyme Assaymentioning
confidence: 99%